Fünf- bis Zehn-Jahresergebnisse für den Oberflächenersatz des Hüftgelenks: eine systematische Literaturanalyse der mittelfristigen Standzeiten = Results of 5 to 10-year follow-up after hip resurfacing : a systematic analysis of the literature on long-term results - Klotz, Matthias C. M.; Breusch, Stephen J.; Hassenpflug, Matthias; Bitsch, Rudi G. (Der Orthopäde, 2012)
Hip resurfacing is a common method for therapy of coxarthritis and is currently under discussion. The aim of this study was to analyze hip resurfacing follow-up studies with more than 5 years follow-up time. A total of 17 studies which matched the inclusion criteria were analyzed. The survival rate after 5-6 years was 96.3%, after 7-8 years 93.8% and after 9-10 years 90%. Young men with primary coxarthritis and surgery by an experienced surgeon showed the best results. The main causes for revision were aseptic loosening with 34.4% and fracture of the proximal femur with 31.9%. Dislocation as a cause for revision was rare and occurred in 2.8% of all cases. Hip resurfacing showed worse results than conventional hip arthroplasty. The risk for complications was high especially for women, with small prostheses and in patients with suboptimal positioning of the prosthesis.
Paralleltitel von der Frontdoor übernommen
Gesehen am 26.10.2018